Marginalization and Precariat: The Challenge of Intensifying Life Construction Intervention - Di Fabio, Annamaria; Palazzeschi, Letizia (Frontiers in Psychology, 2016)
This article discusses the case study of a graduate student who, at the time of the study, was doing an internship, considered in the literature as a new form of precariat (temporary or insecure employment). The student participated in a life construction intervention during which he completed two new qualitative instruments: the Life Adaptability Qualitative Assessment (LAQuA) and the Career Counseling Innovative Outcomes (CCIO) before and after the life construction intervention. The results are discussed in the article. The life construction intervention helped the participant understand himself better, develop his life and career paths, and construct his identity. The study confirmed the value of enhancing life construction interventions using a preventive approach, particularly for precarious people (people in temporary or unstable jobs), with early interventions starting with young internees in organizations.